PENGARUH KINERJA STRATEGI PRODUK, HARGA, PROMOSI, LOKASI, PROCESS, PEOPLE, DAN PHYSICAL EVIDENCE TERHADAP KEPUTUSAN PEMBELIAN DODOL ANEKA BUAH PADA UD. EDELWEIS - I GUSTI AGUNG DIDIT EKA PERMADI; LUH UTAMI; SYAHRUL SYAHRUL; MOHAMMAD ADE SAKBANI; ROMI DWIKI HILMI; I DEWA GEDE SUARTHA (GANEC SWARA, 2023)
The purpose of this study was to analyze the effect of the performance of product strategy, price, promotion, location, process, people, and physical evidence simultaneously and partially on the purchasing decision of various fruit dodol at UD. Edelweiss in Selat Village, Narmada District, West Lombok Regency and the most dominant variable influencing the decision to buy various fruit dodol at UD. Edelweis in Selat Village, Narmada District, West Lombok Regency. This research is associative research. The sampling method in this study was non-probability sampling using saturated sampling techniques. Data collection techniques in this study were interviews and questionnaires. Data collection tool used is a questionnaire. The collected data were analyzed using Multiple Linear Regression Analysis. The conclusion obtained is that the performance of product strategy, price, promotion, location, process, people, and physical evidence has a significant positive effect simultaneously and partially on the decision to buy various fruit dodol at UD. Edelweiss in Selat Village, Narmada District, West Lombok Regency and location has the most dominant influence on the decision to purchase various fruit dodol at UD. Edelweis in Selat Village, Narmada District, West Lombok Regency.